Squaric acid-based polymers, their preparation and their use
By using polymers containing specific conjugated non-aromatic cyclic groups in lithium-ion batteries, high voltage insertion of lithium ions is achieved, solving the problem of insufficient energy and power density of lithium ion batteries in the prior art, and improving the performance of the battery.
Patent Information
- Application Number
- JP2020556790
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-07-19
- Filing Date
- 2019-04-30
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2039-04-30
AI Technical Summary
The prior art is difficult to implement lithium insertion in lithium-ion batteries at high voltages, limiting the development of high-energy, high-power, rechargeable and dischargeable lithium-ion batteries.
Using a polymer containing a specific conjugated non-aromatic cyclic group, a polymer electrolyte with high charge density and high conductivity is formed by reacting with lithium ions to achieve high voltage insertion of lithium ions.
High voltage insertion of lithium ions is achieved, the energy density and power density of lithium ion batteries are improved, and the polymer electrolyte has good conductivity and stability.
Smart Images

Figure 0007674104000045 
Figure 0007674104000046 
Figure 0007674104000047
Abstract
Description
[Technical field]
[0001] Related Applications This application claims priority under applicable law to U.S. Provisional Application No. 62 / 664,611, filed April 30, 2018, and U.S. Provisional Application No. 62 / 700,554, filed July 19, 2018, the entire contents of which are incorporated by reference herein for all purposes.
[0002] Technical Field The technical field generally relates to polymers comprising monomer units derived from squaric acid, their preparation methods and their use in electrochemical cells, for example in organic polymer-based electrode materials and / or polymer electrolytes. [Background technology]
[0003] background Until recently, replacing inorganic intercalation compounds in lithium-ion batteries with organic polymer-based electrode materials has not been considered a promising alternative. This is in part because most organic polymer-based electrode materials intercalate lithium at low voltages (<4 V) (see (a)Muench, S. et al., Chemical Reviews 116.16 (2016): 9438-9484; (b)Peng, C. et al., Nature Energy 2.7 (2017): 17074; and (c)Xu, F. et al., Electrochemistry Communications 60 (2015): 117-120), which precludes the development of high-energy and high-power rechargeable batteries. Furthermore, a good electrode material needs to be both ionically and electronically conductive (Peng, C. et al., see above).
[0004] Considering that the raw materials used are obtained from renewable resources, the organic active materialThe use of these materials may reduce the environmental footprint of the battery (Armand, M. and Tarascon, JM., Nature 451.7179 (2008): 652). These materials may also be used with a variety of ionic species, such as sodium, lithium, and magnesium. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Muench, S. et al., Chemical Reviews 116.16 (2016): 9438-9484 [Non-Patent Document 2] Peng, C. et al., Nature Energy 2.7 (2017): 17074 [Non-Patent Document 3] Xu, F. et al., Electrochemistry Communications 60 (2015): 117-120 [Non-Patent Document 4] Armand, M. and Tarascon, JM., Nature 451.7179 (2008): 652 Summary of the Invention [Problem to be solved by the invention]
[0006] Thus, there is a need for such alternative organic polymer-based electrode materials that exhibit improved properties, such as lithium intercalation at high voltages. [Means for solving the problem]
[0007] According to a first aspect, the present technology provides a compound of formula I: [ka] (In the formula, n and m are integers representing the number of each monomer unit in the polymer, where n>2 and m>0; X, in each occurrence, is independently an oxygen atom, a sulfur atom, and an amine group (NR X ), p is an integer representing the number of X groups in each monomer unit, where p is 0 or 1; R 1 is an optionally substituted conjugated non-aromatic cyclic group such as a quinone group, an optionally substituted aromatic or partially aromatic organic group, or combinations thereof in a polycyclic group; R x is a hydrogen atom or an optionally substituted alkyl. The present invention relates to a polymer.
[0008] According to another aspect, the present technology relates to a polymer as defined herein for use in an electrode material and / or electrolyte composition in an element of an electrochemical cell.
[0009] According to another aspect, the present technology provides a method for producing a polymer as defined herein, comprising the steps of: (a) Formulas II and III: [ka] (In the formula, X and R 1 is as defined herein; Y is independently selected in each occurrence from a halogen atom, a hydroxyl group, an amine group, and a lower alkoxy group; q is an integer representing the number of nucleophilic groups of the second monomer unit and is at least 2; and reacting the monomer units of (b) isolating the polymer produced in step (a); The present invention relates to a method comprising the steps of:
[0010] In one embodiment, Y is independently at each occurrence a chlorine atom, a bromine atom, an iodine atom, an amine group, a hydroxyl group, or a lower alkoxy group, e.g., the monomer unit of formula II is selected from 3,4-dihydroxy-3-cyclobutene-1,2-dione, 3,4-dimethoxy-3-cyclobutene-1,2-dione, 3,4-diethoxy-3-cyclobutene-1,2-dione, 3,4-diisopropoxy-3-cyclobutene-1,2-dione, 3,4-dibutoxy-3-cyclobutene-1,2-dione, 3,4-diamino-3-cyclobutene-1,2-dione, 3,4-dichloro-3-cyclobutene-1,2-dione, 3,4-dibromo-3-cyclobutene-1,2-dione, and 3,4-diiodo-3-cyclobutene-1,2-dione. In another embodiment, step (a) is carried out in the presence of an organic base, for example the organic base comprises a tertiary amine, for example triethylamine, 2,6-lutidine or pyridine, preferably pyridine.
[0011] In another embodiment, step (a) is carried out in the presence of a Lewis acid, for example, the Lewis acid is selected from the group consisting of boron trifluoride etherate (BF3.OEt2), tin tetrachloride (SnCl4), zinc chloride (ZnCl2) and metal trifluoromethanesulfonate (triflate), preferably zinc trifluoromethanesulfonate (zinc triflate).
[0012] In another embodiment, step (a) is carried out in the presence of a solvent and step (b) further comprises removing the organic polar aprotic solvent by evaporation.
[0013] In another embodiment, the polymer is produced by a polycondensation reaction.
[0014] According to another aspect, the present technology provides a method for producing a polymer as defined herein, comprising the steps of: (a) Formulas II and IV: [ka] (In the formula, R 1 is as defined herein; Y, independently in each occurrence, is a leaving group selected from a chlorine atom, a bromine atom, and an iodine atom; Z is independently in each occurrence selected from the group consisting of chlorine atoms, bromine atoms, iodine atoms, boronic acids, boronic esters, and trialkyltin groups; r is an integer representing the number of Z monomer units of formula IV and is at least 2; and reacting the monomer units of (b) isolating the polymer produced in step (a); The present invention relates to a method comprising the steps of:
[0015] In another embodiment, step (a) further comprises reacting the monomeric unit of formula II with magnesium, thereby forming a Grignard reagent in situ prior to the addition of the monomeric unit of formula IV.
[0016] In another embodiment, step (a) is carried out in the presence of a catalyst. For example, the catalyst comprises a compound comprising a transition metal, a transition metal, or a coordination complex comprising a transition metal. For example, the transition metal is selected from the group consisting of Ni, Pd, Co, Fe, Cr, Cu, and Mn, and is preferably Ni or Pd. For example, the catalyst may further comprise trialkylphosphine or triphenylphosphine (PPh3), tetrahydrofuran (THF), 2,2'-bipyridine (bpy), copper(I) iodide (CuI) or potassium fluoride (KF). In some cases, for example, when Z is a boronic ester, the reaction may proceed in an ionic liquid without an additional catalyst.
[0017] According to another aspect, the present technology relates to an electrode material comprising a polymer as defined herein. For example, the electrode material is a positive electrode material and is electrochemically active material and optionally a binder, or optionally an electronically conductive material, or a combination thereof. For example, the polymer may be used as a binder or an electrochemically conductive material. active materialAlternatively, the polymer can be electrochemically active material For example, electrochemical active material Both the binder and the binder comprise said polymer.
[0018] In another embodiment, the electrode material further comprises a transition metal oxide, for example, the transition metal is selected from the group consisting of titanium (Ti), manganese (Mn) and cobalt (Co).
[0019] According to another aspect, the present technology relates to a positive electrode comprising an electrode material as defined herein on a current collector.
[0020] According to another aspect, the present technology relates to an electrolyte composition comprising a polymer and a salt as defined herein. For example, the electrolyte is a solid polymer electrolyte (SPE) or a gel electrolyte.
[0021] According to a further aspect, the present technology relates to an electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein at least one of the positive electrode and the electrolyte comprises a polymer as defined herein.
[0022] According to a further aspect, the present technology relates to an electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein the electrolyte is as defined herein.
[0023] According to a further aspect, the present technology relates to a battery comprising at least one electrochemical cell as defined herein.
[0024] According to yet a further aspect, the present technology relates to a polymer as defined herein for use in a polymer-based optoelectronic device, for example, the polymer-based optoelectronic device is selected from the group consisting of an electrochromic device (ECD), a photochromic device, an organic light-emitting diode (OLED) and a solar cell. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 shows an attenuated total reflectance Fourier transform infrared spectrum (ATR-FTIR) of a copolymer according to one embodiment, as described in Example 2(e).
[0026] [Diagram 2] FIG. 2 shows a solid-state 13C nuclear magnetic resonance (NMR) spectrum of a copolymer according to one embodiment, as described in Example 2(f).
[0027] [Diagram 3] FIG. 3 shows an ATR-FTIR spectrum of a copolymer according to one embodiment, as described in Example 2(f).
[0028] [Figure 4] FIG. 4 shows a cyclic voltammogram of a copolymer according to one embodiment, as described in Example 3(a).
[0029] [Diagram 5] FIG. 5 shows a cyclic voltammogram of a copolymer according to one embodiment, as described in Example 3(b). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The following detailed description and examples are illustrative and should not be construed as further limiting the scope of the invention.
[0031] All technical and scientific terms and expressions used herein have the same definitions as those commonly understood by those skilled in the art when related to the present technology. Nevertheless, for the sake of clarity, definitions of some terms and expressions used herein are provided below.
[0032] The term "approximately" or its equivalent "about" as used herein means approximately, or in the vicinity, and approximately. When the term "approximately" or "about" is used in reference to a numerical value, it modifies the numerical value. For example, it may mean above or below its nominal value by a variance of 10%. This term may also take into account the possibility of random error or rounding in experimental measurements.
[0033] For greater clarity, as used herein, the phrase "monomer unit derived from" and equivalent phrases refer to a repeat unit of a polymer that results from a polymerizable monomer after polymerization.
[0034] The chemical structures described herein are drawn according to conventional standards, and when a depicted atom, such as a carbon atom, appears to contain incomplete valences, it is assumed that the valences are satisfied by one or more hydrogen atoms, even if not necessarily explicitly depicted.
[0035] As used herein, the phrase "leaving group" refers to a group that can be displaced along with its bonding electrons by a nucleophile in a chemical reaction. Representative leaving groups include halogens, alkoxy, tosylates, iodides, bromides, chlorides, and the like.
[0036] As used herein, the term "alkyl" refers to a saturated hydrocarbon having 1 to 12 carbon atoms, including straight-chain or branched alkyl groups. Examples of alkyl groups include, without limitation, methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, tert-butyl, sec-butyl, isobutyl, and the like. When an alkyl group is located between two functional groups, the term "alkyl" also encompasses alkylene groups such as methylene, ethylene, propylene, and the like. The term "lower alkyl" refers to an alkyl group having 1 to 6 carbon atoms.
[0037] As used herein, the term "alkoxy" refers to an alkyl group having an oxygen atom attached thereto. Representative alkoxy groups include groups having 1 to about 12 carbon atoms. Examples of alkoxy groups include methoxy, ethoxy, isopropyloxy, propoxy, isopropoxy, butoxy, isobutoxy, tert-butoxy, pentoxy groups, and the like. The term "lower alkoxy" refers to an alkoxy group having 1 to 6 carbon atoms.
[0038] The expression "aromatic group" is intended to include delocalized conjugated π systems containing a number of delocalized π electrons equal to 4n+2 π electrons. The contributing atoms may be arranged in one or more rings. Representative aromatic groups include 5- and 6-membered carbon monocyclic rings. Aromatic groups may contain one or more fused benzene rings, e.g., benzene, naphthalene, anthracene, and the like. The expression "aromatic group" also includes aromatic groups containing one or more heteroatoms, such as sulfur, oxygen, and nitrogen atoms. When at least one heteroatom is present, the aromatic group may be referred to as a "heteroaromatic group." The aromatic ring may be further substituted at one or more ring positions, e.g., with hydroxyl, amine, and the like.
[0039] As used herein, the term "quinone" refers to a cyclic conjugated group of aromatic origin that contains at least two carbonyl groups (i.e., a dione). These compounds can be considered to have two C=O groups, with each carbon being part of a cyclic ring structure of a fully conjugated structure. Representative quinones include 1,2-benzoquinone, 1,4-benzoquinone, naphthoquinone, anthraquinone, and the like. Each quinone group may be further substituted with or be part of a larger group, e.g., a polycyclic group.
[0040] As used herein, the phrase "polycyclic group" refers to an organic group that contains at least two rings joined together by a covalent bond or by sharing at least two ring atoms (fused rings).
[0041] As used herein, the phrase "optionally substituted" refers to functional groups other than hydrogen atoms that may not adversely affect the preparation of the polymer. Examples of such groups depend on the polymerization conditions and may include groups such as lower alkyl, lower alkoxy, nitrile, fluorine atom, chlorine atom, nitrile, C3-C6 cycloalkyl, C3-C6 heterocycloalkyl, amide, amine, sulfone, sulfonamide, silyl, etc. Alkyl, alkoxy, cycloalkyl, and heterocycloalkyl may be further substituted, for example, as halogenated lower alkyl (e.g., CF3) or halogenated lower alkoxy (e.g., OCF3).
[0042] The present technology relates to polymers or copolymers comprising monomer units derived from squaric acid, such as poly(squarylamides) (see Neuse, EW et al., Polymer 15.6 (1974): 339-345) and poly(squaryl esters). For example, such polymers are intended for use in electrochemical cells. For example, the polymers are for use in electrode materials or as part of electrolyte compositions, such as solid or gel polymer electrolytes. Such polymers are useful in the cathode electrochemical synthesis of organic Li-ion batteries. active material This polymer allows the battery to be cycled at high voltages (greater than 3.8 V). In addition, the polymer is electronically and ionically conductive. The polymerization step is relatively low cost and easy to scale up. The polymer can be designed by choosing the monomers used for copolymerization with squaric acid. This versatility allows the voltage of the reaction to be tuned.
[0043] According to a first aspect, the present technology provides a compound of formula I: [ka] (In the formula, n and m are integers representing the number of each monomer unit in the polymer, where n>2 and m>0; X, in each occurrence, is independently an oxygen atom, a sulfur atom, and an amine group (NR X ), p=0 or 1, R 1 is an optionally substituted conjugated non-aromatic cyclic group such as a quinone group, an optionally substituted aromatic or partially aromatic organic group, or combinations thereof in a polycyclic group; R x is a hydrogen atom or an optionally substituted alkyl group. The present invention relates to a polymer.
[0044] For example, the aromatic or partially aromatic organic group is a cyclic or polycyclic aromatic or partially aromatic organic group. The monocyclic or polycyclic aromatic or partially aromatic organic group may be derived, for example, from one or more fused benzene rings, or one or more fused 5- or 6-membered rings, or a combination thereof. The monocyclic or polycyclic aromatic or partially aromatic organic group may be, for example, a heterocyclic group, for example, a heteroaromatic group. Alternatively, the partially aromatic organic group comprises a quinone moiety.
[0045] For example, the monocyclic or polycyclic aromatic or partially aromatic organic group is derived from benzene, naphthalene, anthracene, thiophene, thienopyrroledione, benzothiophene, benzothiadiazole, 3,4-ethylenedioxythiophene, carbazole, dithiophene anthranthrone, dithiophenediketopyrrolopyrrole, isoindigo or indigo.
[0046] For example, R 1 When is a heterocyclic group, each heterocycle may contain 1 to 3 heteroatoms selected from nitrogen, sulfur and oxygen atoms, preferably nitrogen or sulfur atoms. The heterocyclic group contains at least one aromatic or heteroaromatic group.
[0047] For example, R 1When is a substituted group, said group is substituted with one or more alkyl groups, alkoxy groups, nitrile groups, hydroxyl groups, halogen atoms, or, if attached to a heteroatom such as a nitrogen atom, a protecting group.
[0048] For example, R x When is a substituted alkyl group, said alkyl group may be substituted with a crosslinkable moiety.
[0049] In one example, m is 0 and the polymer of formula I is a squaric acid based homopolymer. In another example, m is different from 0 and the polymer of formula I is a copolymer, e.g., an alternating copolymer.
[0050] In some of the polymers described herein, p is different from 0 and X is an oxygen atom in all cases, i.e., polyester polymers. Alternatively, p is different from 0 and X is an amine group in all cases, i.e., polyamide polymers. In other cases, p is 0 and X is absent.
[0051] In other examples of polymers of Formula I where n is greater than 2, more than two, or more than three, squaric acid-containing monomers or chains of monomers are present in R 1 may be bonded to, i.e., R 1 may be attached via an X group or directly to one, two, three or more squaric acid monomer units.
[0052] For example, the polymer of formula I is either a homopolymer or a copolymer prepared from monomer units derived from formula II. Thus, the polymer comprises at least one monomer unit of formula II: [ka] wherein Y in each occurrence is independently selected from a halogen atom, a hydroxyl group, an amine group, and a lower alkoxy group. It is prepared by reacting monomer units derived from squaric acid of
[0053] For example, Y is selected from the group consisting of chlorine, bromine and iodine atoms, hydroxyl groups, amine groups and lower alkoxy groups. In another example, Y is a leaving group selected from chloride and bromide, preferably chloride.
[0054] Non-limiting examples of monomer units derived from squaric acid of formula II include 3,4-dihydroxy-3-cyclobutene-1,2-dione, 3,4-dimethoxy-3-cyclobutene-1,2-dione, 3,4-diethoxy-3-cyclobutene-1,2-dione, 3,4-diisopropoxy-3-cyclobutene-1,2-dione, 3,4-dibutoxy-3-cyclobutene-1,2-dione, 3,4-diamino-3-cyclobutene-1,2-dione, 3,4-dichloro-3-cyclobutene-1,2-dione, 3,4-dibromo-3-cyclobutene-1,2-dione and 3,4-diiodo-3-cyclobutene-1,2-dione.In one variant of interest, the monomer unit derived from squaric acid of formula II is 3,4-dichloro-3-cyclobutene-1,2-dione.
[0055] In one embodiment, the polymer comprises monomer units of formula II above and monomer units of formula III: [ka] (In the formula, X and R 1 is as defined herein, and q is an integer representing the number of each nucleophilic group (XH) of the second monomer unit, which is at least 2. with a second monomer unit of
[0056] Thus, the second monomer unit of formula III is a polyfunctional nucleophilic reactant having at least two nucleophilic groups (XH). In one variation of interest, the nucleophilic group XH may be either an alcohol, a thiol, or a primary amine group (NH2).
[0057] Non-limiting examples of the second monomer unit of formula III include p-phenylenediamine (PPD), benzene-1,4-diol, 5,8-dihydroxy-1,4-naphthoquinone, 5,6-dihydroxycyclohex-5-ene-1,2,3,4-tetrone, tetrahydroxy-1,4-benzoquinone, 1,4-diamino-2,3-dihydroanthraquinone and 4,5-dihydroxycyclopentene trione.For example, the second monomer unit of formula III is benzene-1,4-diol or 1,4-diamino-2,3-dihydroanthraquinone.
[0058] Examples of the second monomer unit of formula III are represented by formulae III(a) through III(g): [ka] This includes compounds of the formula:
[0059] Alternatively, the polymer may comprise monomer units of formula II and monomer units of formula IV, as defined below. [ka] (In the formula, R 1 is as defined herein, Z is independently at each occurrence selected from the group consisting of chlorine, bromine, iodine, boronic acid, boronic ester, and trialkyltin groups, preferably a bromine atom, and r is an integer representing the number of Z in formula IV and is at least 2. with a second monomer unit of
[0060] For example, Z is a halogen atom selected from chlorine, bromine and iodine atoms. In another example, Z is selected from B(OH)2, B(Oalkyl)2 and cyclic boronic esters (e.g., pinacol boronic esters). In a further example, Z is a trialkyltin group, such as tri-n-butyltin.
[0061] Non-limiting examples of second monomer units of formula IV include those of formulas IV(a)-IV(j): [ka] [ka] (In the formula, Z is as defined herein; R 2 is an amine protecting group, R 3 is independently at each occurrence a substituent selected from an alkyl group, an alkoxy group, a nitrile group, a hydroxyl group, and a halogen atom, preferably C 6~7 Alternatively, R 3 is a hydrogen atom) This includes compounds of the formula:
[0062] For example, R 2 is tert-butoxycarbonyl (BOC), carbobenzyloxy (CBz), p-methoxybenzyl (PMB) or benzyl (Bn), acetyl (Ac), benzoyl (Bz), preferably R 2 is BOC.
[0063] Non-limiting examples of second monomer units of formula IV also include those of formulas IV(k)-IV(o): [ka] wherein Z is as defined herein. The compound may include:
[0064] When the polymer is a copolymer, the copolymer may be, for example, an alternating, random or block copolymer. The copolymer may be linear or branched (e.g., star, comb, etc.). In one variation of interest, the copolymer is an alternating copolymer.
[0065] According to another aspect, the present technology also relates to a method for producing the polymer defined herein. The polymerization of monomers may be achieved by any known procedure. For example, when the polymer forms a homopolymer, the monomer units derived from squaric acid may be linked together by a nucleophilic moiety, i.e., an oxygen atom or an amine group (NH).
[0066] Polymerization of the monomers may be accomplished by any known procedure. For example, it may be accomplished by polycondensation. When the polymer is a copolymer, polymerization occurs between the repeating monomer units derived from squaric acid of formula II and the monomer units of formula III. When the polymer is a copolymer, the polymerization may be performed as shown in Scheme 1: [ka] (In the formula, Y, R 1 , X, q, n and m are as defined herein, and p is 1. They may also be prepared by the polymerization method shown in .
[0067] When the polymer is a homopolymer, polymerization occurs between monomer units derived from squaric acid of formula II. A homopolymer can be prepared according to Scheme 2a or 2b: [ka] They may also be prepared by the polymerization method shown in .
[0068] According to one example, polycondensation is the process of forming condensed molecules (H + Y - The polycondensation reaction is carried out in the presence of an organic base that is added to capture the amines (A, B, C, D, E ...
[0069] According to one example, the polycondensation is carried out in the presence of an organic polar aprotic solvent, for example, the organic polar aprotic solvent is selected from dimethylformamide (DMF), dimethylsulfoxide (DMSO), and the like.
[0070] According to another example, XH is a primary amine group, and polycondensation is carried out in the presence of a Lewis acid added as a catalyst. The Lewis acid catalyst can promote the polycondensation of the second monomer unit of formula III by suppressing the formation of squaraine by-products using squaric acid esters, such as diethoxy-3-cyclobutene-1,2-dione (or diethyl squarate). The by-product of the polycondensation promoted by Lewis acid is an alcohol, such as ethanol. Non-limiting examples of Lewis acid catalysts include boron trifluoride etherate (BF3.OEt2), tin tetrachloride (SnCl4), zinc chloride (ZnCl2), and trifluoromethanesulfonic acid metal salts (triflates). Non-limiting examples of metal trifluoromethanesulfonates include scandium(III) trifluoromethanesulfonate (Sc(OTf)3), magnesium trifluoromethanesulfonate (Mg(OTf)2), copper trifluoromethanesulfonate (Cu(OTf)2), and zinc trifluoromethanesulfonate (Zn(OTf)2). For example, a Lewis acid is zinc trifluoromethanesulfonate (zinc triflate).
[0071] According to one example, the Lewis acid promoted polycondensation is carried out in the presence of a mixture of organic polar aprotic and non-polar solvents, for example, the solvents include toluene and dimethylformamide.
[0072] Alternatively, polymerization may be accomplished by organometallic chemical reactions such as Grignard reactions. For example, polymerization of monomers by coupling Grignard reagents with aryl halides. For example, Grignard reagents are prepared by reacting repeating monomer units derived from squaric acid of formula II, in which the leaving group is a halogen atom, with magnesium. For example, the leaving group is a halogen atom, independently selected from the group consisting of chloride, bromide, and iodide, at each occurrence, and preferably a chlorine atom.
[0073] The polymer is then produced by subsequent reaction of the prepared Grignard reagent with a monomer unit derived from squaric acid of formula II or a monomer unit of formula IV to produce homopolymers and copolymers, respectively. When the polymer is a copolymer, Scheme 3: [ka] When the polymer is a homopolymer, it may be prepared by the polymerization method shown in Scheme 4: [ka] They may also be prepared by the polymerization method shown in .
[0074] According to one example, the Grignard reaction is carried out in the presence of a catalyst. For example, the catalyst comprises a transition metal or a compound containing a transition metal. For example, the transition metal is selected from the group consisting of nickel, palladium, cobalt, iron, chromium, copper and manganese, preferably nickel or palladium. For example, the catalyst may be a complex. For example, the complex comprises triphenylphosphine (PPh3) or 2,2'-bipyridine (bpy). Non-limiting examples of catalysts include NiCl2(bpy), NiBr2(PPh3)2, PdCl2(bpy), Pd2(dba)3, Pd(PPh3)4, Pd(PPh3)2Cl2, FeEt2(bpy)2, CrMeCl2(THF)3, bis(1,5-cyclooctadiene)nickel (Ni(COD)2)(PPh3)2, FeCl2, FeCl3 and CoCl2. For example, the catalyst comprises a complex of Ni(COD)2 and PPh3 in a 1:2 ratio.
[0075] According to one example, the Grignard reaction is carried out in the presence of an organic polar aprotic solvent, which can be, for example, tetrahydrofuran (THF).
[0076] Alternatively, polymerization may be accomplished by dehalogenation polymerization of a haloaromatic compound, or by cross-coupling of a haloaromatic compound with an activated compound, such as a trialkyltin compound or a boronic acid or boronic acid ester compound. Dehalogenation polymerization is the reaction of a repeating monomer unit derived from squaric acid of formula II, in which the leaving group is a halogen atom, with a haloaromatic compound. For example, the haloaromatic compound may be a di- or polyhalogenated aromatic compound. For example, the haloaromatic compound is of formula IV. For example, the halogen atom is independently selected from the group consisting of Cl, Br and I at each occurrence, and is preferably Cl or Br. Similarly, cross-coupling may be accomplished by reacting a repeating monomer unit derived from squaric acid of formula II, in which the leaving group is a halogen atom, with an aromatic compound containing a trialkyltin, boronic acid or boronic acid ester moiety, for example, a monomer unit of formula IV, in which Z is a trialkyltin, boronic acid or boronic acid ester group. For example, the aromatic compound is derived from benzene or a heteroaromatic group. If the polymer is a copolymer, Scheme 5: [ka] They may also be prepared by the polymerization method shown in .
[0077] Non-limiting examples of aromatic compounds of formula IV include compounds of formula IV(j), IV(k), IV(l), IV(m), IV(n), IV(o) or IV(p). For example, the aromatic compound is selected from the group consisting of p-dibromobenzene, p-dichlorobenzene, m-dichlorobenzene, m-dibromobenzene, o,p-dichlorotoluene, 2,5-dibromopyridine, 9,10-dibromoanthracene, 1,3,5-trichlorobenzene, 2,5-dibromothiophene, thiophene-2,5-diboronic acid, thiophene-2,5-diboronic acid ester (e.g., bis(pinacol) ester), 2,5-bis(trialkyltin)thiophene (e.g., 2,5-bis(n-butyltin)thiophene).
[0078] According to an example, the polymerization with aromatic compounds may be carried out in the presence of a catalyst. For example, the catalyst is in excess compared to the monomer. For example, the catalyst comprises a transition metal or a compound containing a transition metal. For example, the transition metal is selected from the group consisting of Ni, Pd, Co, Fe, Cr, Co and Mn, preferably Ni or Pd. For example, the catalyst may be a complex. For example, the complex comprises triphenylphosphine (PPh3) or 2,2'-bipyridine (bpy). Examples of catalysts also include NiCl2(bpy), NiBr2(PPh3)2, PdCl2(bpy), Pd2(dba)3, Pd(PPh3)4, Pd(PPh3)2Cl2, FeEt2(bpy)2, CrMeCl2(THF)3, and bis(1,5-cyclooctadiene)nickel (Ni(COD)2)(PPh3)2. For example, the catalyst may be generated in situ. For example, the catalyst comprises Ni(COD)2, 1,5-cyclooctadiene and bpy catalyst in a ratio of 1:1:1. For example, the catalyst may further comprise trialkylphosphine or triphenylphosphine (PPh3), tetrahydrofuran (THF), 2,2'-bipyridine (bpy), CuI or KF. In some cases, such as when Z is a boronic acid ester, the reaction may proceed in ionic liquid without additional catalyst. A polymerization method using ionic liquid is shown in Page, ZA et al., Chem. Sci., 2014, Vol. 5, 2368-73.
[0079] According to one example, the polymerization with the aromatic compound is carried out in the presence of a non-polar solvent, which may be, for example, toluene.
[0080] The method described herein can be considered to be inexpensive and easy to scale up polymerization method compared to other existing methods.The polymerization method described herein is also much safer than the method presented by Neuse, EW et al. (see above).For example, the method described herein does not use hot polyphosphoric acid.Another advantage is that the polymer can be designed by the monomer used in copolymerization with squaric acid, and this versatility allows voltage adjustment by changing reaction conditions and monomer used.
[0081] Also contemplated are polymers obtainable by the methods described herein that include any combination of a monomer derived from squaric acid with any of the second monomers. Non-limiting examples of polymers of the invention include: [ka] [ka] (wherein Ar is an aryl divalent group). Includes.
[0082] The polymers described herein are contemplated for use in components of electrochemical cells, i.e., electrode materials and / or electrolyte compositions.
[0083] According to another aspect, the present technology also relates to an electrode material comprising the polymer defined herein. In one variant of the subject matter, the electrode material is a positive electrode material. In one embodiment, the positive electrode material is an electrochemically active material , optionally a binder, optionally an additive, optionally an electronically conductive material, or combinations thereof.
[0084] The electrode material may also optionally include additional components such as conductive materials, salts, inorganic particles, glass or ceramic particles, etc. Examples of conductive materials include carbon black, Ketjen™ black, acetylene black, graphite, graphene, carbon fibers, nanofibers (e.g., VGCF), or carbon nanotubes, or combinations thereof.
[0085] In one example, the polymers described herein are used in electrode materials as binders. Alternatively, the polymers may be used in electrochemical active material Polymers are also used as binders and electrochemically active agents in electrode materials. active material It can act as both.
[0086] In one example, the polymers described herein can be electrochemically active material For example, electrochemical active material is selected from the group consisting of metal oxide particles, lithiated metal oxide particles, metal phosphate particles, and lithiated metal phosphate particles. For example, the metal is a transition metal selected from the group consisting of titanium (Ti), iron (Fe), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), and combinations of at least two thereof.
[0087] In another example, the electrochemically active electrode material may further comprise an oxide of a transition metal, for example, the transition metal is selected from the group consisting of titanium (Ti), manganese (Mn), cobalt (Co), and the like. According to another aspect, the present technology also relates to a positive electrode comprising the electrode material defined herein. For example, the positive electrode comprises the electrode material on a current collector. The present technology also contemplates an electrolyte composition comprising a polymer and a salt defined herein. For example, the electrolyte may be a gel or solid polymer electrolyte. When the electrolyte is a gel electrolyte, a separator may further be added.
[0088] According to another aspect, the present technology also relates to an electrochemical cell comprising the polymer of the present invention. Such an electrochemical cell comprises a negative electrode, a positive electrode and an electrolyte, and at least one of the positive electrode and the electrolyte comprises the polymer of the present invention. In one example, the positive electrode comprises an electrode material as defined herein. In another example, the electrolyte comprises an electrolyte composition as defined herein. In another example, the electrode comprises an electrode material as defined herein, and the electrolyte comprises an electrolyte composition as defined herein.
[0089] To be more clear, the electrochemical active material is the electrochemical active material (electrode active material The negative electrode material may be selected from any known material, including anode materials such as lithium metal, lithium ion batteries ...
[0090] According to another aspect, a battery is described that includes at least one electrochemical cell as defined herein. For example, the battery is selected from the group consisting of a lithium battery, a sodium battery, and a magnesium battery.
[0091] According to another aspect, the polymers described herein are contemplated for use in polymer-based optoelectronic devices, such as electrochromic devices (ECDs), photochromic devices, organic light emitting diodes (OLEDs) and solar cells. EXAMPLES
[0092] The following non-limiting examples are illustrative embodiments and should not be construed as further limiting the scope of the present invention. These examples are better understood with reference to the accompanying drawings. Example 1 Preparation of homopolymers (a) Polycondensation of squaric acid and squaryl dichloride - synthesis of squaric acid homopolymer (poly(squaric acid ester)) [ka]
[0093] This example illustrates the polycondensation of squaric acid with squaryl dichloride (1,2-dichlorocyclobutene-3,4-dione). To carry out this polycondensation, 1 g of squaric dichloride and 0.75 g of squaric acid were introduced into a 200 mL Schlenk tube. 30 mL of dry dimethylformamide (DMF) as hydrogen chloride acceptor and 10 mL of dry pyridine were added to the Schlenk tube under inert atmosphere. The reaction was then stirred at room temperature with a magnetic bar for 3 days. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was vigorously stirred for 15 minutes. The solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60° C. for 12 hours. (b) Homopolymerization of squaryl dichloride - synthesis of squaric acid homopolymer [ka] - Preparation of Grignard Reagent Solution
[0094] Add 30 mL of anhydrous tetrahydrofuran (THF) to a nitrogen (N2) purged three-neck round bottom flask anhydrous reactor, add (0.322 g, 13.2 mmol) freshly etched dry magnesium turnings to the reactor, and purge the resulting suspension with N2. Prepare a solution of (1.00 g, 6.62 mmol) 3,4-dichloro-3-cyclobutene-1,2-dione in 10 mL of anhydrous THF and add it continuously to the magnesium turnings suspension in the reactor over 1 h using a cannula under N2 atmosphere. The resulting Grignard reagent solution is then heated at reflux at 70 °C for 1 h, cooled to room temperature, and degassed under N2 atmosphere. - Preparation of Squaryl Dichloride Solution
[0095] Add 10 mL of anhydrous tetrahydrofuran (THF) to a second three-neck round bottom flask anhydrous reactor purged with nitrogen (N2), add (1.00 g, 6.62 mmol) of 3,4-dichloro-3-cyclobutene-1,2-dione to the second reactor, and degas the resulting solution using N2. Then add (0.09 g, 0.331 mmol) of bis(1,5-cyclooctadiene)nickel (Ni(COD)2) and (0.173 g, 0.662 mmol) of triphenylphosphine (PPh3) to the resulting solution, and purge the reactor with N2. - Preparation of polymers
[0096] The Grignard reagent solution prepared in the first step is added to the squaryl dichloride solution prepared in the second step using a cannula under N2 atmosphere. The resulting solution is then heated to about 70°C under reflux for 16 hours. The reaction is precipitated with a 10:1 v / v solution of methanol and water, and the polymer is recovered by filtration. (c) Homopolymerization of squaryl dichloride - synthesis of squaric acid homopolymer [ka] - Preparation of Grignard Reagent Solution
[0097] Add 30 mL of anhydrous tetrahydrofuran (THF) to a nitrogen (N2) purged three-neck round bottom flask anhydrous reactor, add (0.161 g, 6.62 mmol) freshly etched dry magnesium turnings to the reactor, and purge the resulting suspension with N2. Prepare a solution of (1.00 g, 6.62 mmol) 3,4-dichloro-3-cyclobutene-1,2-dione in 10 mL of anhydrous THF and add it continuously to the magnesium turnings suspension in the reactor over 1 h using a cannula under N2 atmosphere. The resulting Grignard reagent solution is then heated at reflux for 1 h at 70 °C, cooled to room temperature, and degassed under N2 atmosphere. - Preparation of Ni(COD)2 solution
[0098] Add 10 mL of anhydrous THF to a second 3-neck round bottom flask anhydrous reactor purged with N2 and degas with N2. Next, add (0.09 g, 0.331 mmol) of bis(1,5-cyclooctadiene)nickel (Ni(COD)2) and (0.173 g, 0.662 mmol) of triphenylphosphine (PPh3) to the THF and purge the reactor with N2. - Preparation of polymers
[0099] The Grignard reagent solution prepared in the first step is added to the Ni(COD)2 solution prepared in the second step using a cannula under N2 atmosphere. The resulting solution is then heated at 70 °C under reflux for 16 h. The reaction is precipitated with a 10:1 v / v solution of methanol and water, and the polymer is recovered by filtration. (d) Homopolymerization of squaryl dichloride - synthesis of squaric acid homopolymer [ka]
[0100] Ni(COD)2 (1 eq.), 1,5-cyclooctadiene (1 eq.) and 2,2'-bipyridine (bpy) (1 eq.) are dissolved in toluene. 3,4-dichloro-3-cyclobutene-1,2-dione (0.03 eq.) is added to the mixture. The reaction is then stirred at 60°C for 96 hours to produce an insoluble polymer. The precipitate is washed with an aqueous ammonia solution, an aqueous solution of ethylenediaminetetraacetic acid disodium salt (EDTA disodium salt) at room temperature, and then with water at a temperature of 50°C. The polymer produced is washed overnight by extraction with chloroform using a Soxhlet, extracted with methanol and filtered through Celite™. The methanol is removed by evaporation to give the title polymer. Example 2 Preparation of copolymers (a) Polycondensation of benzene-1,4-diol and squaryl dichloride - synthesis of poly(squaric acid-alt-p-dihydroxyphenylene) copolymer [ka]
[0101] This example illustrates the polycondensation of hydroquinone with squaryl dichloride. To carry out this polycondensation, 0.88 g of 3,4-dichloro-3-cyclobutene-1,2-dione (squaryl dichloride) and 0.50 g of benzene-1,4-diol were introduced into a 200 mL Schlenk tube. 30 mL of dry dimethylformamide (DMF) as hydrogen chloride acceptor and 10 mL of dry pyridine were added to the Schlenk tube under an inert atmosphere. The reaction was then stirred at a temperature of 60 °C using a magnetic bar for 48 hours. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was vigorously stirred for 15 minutes. The solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60 °C for 12 hours. (b) Polycondensation of 5,8-dihydroxy-1,4-naphthoquinone and squaryl dichloride - synthesis of poly(squaric acid-alt-naphthazarin) [ka]
[0102] This example illustrates the polycondensation of 5,8-dihydroxy-1,4-naphthoquinone (naphthazarin) with squaryl dichloride. To carry out this polycondensation, 0.40 g of 3,4-dichloro-3-cyclobutene-1,2-dione (squaric acid dichloride) and 0.50 g of 5,8-dihydroxy-1,4-naphthoquinone were introduced into a 200 mL Schlenk tube. 30 mL of dry dimethylformamide (DMF) as hydrogen chloride acceptor and 10 mL of dry pyridine were added to the Schlenk tube under an inert atmosphere. The reaction was then stirred for 48 hours at a temperature of 60 °C using a magnetic bar. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was vigorously stirred for 15 minutes. The solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60° C. for 12 hours. (c) Polycondensation of 4,5-dihydroxycyclopent-4-ene-1,2,3-trione and squaryl dichloride - synthesis of poly(squaric acid-alt-4,5-dihydroxycyclopent-4-ene-1,2,3-trione) [ka]
[0103] This example illustrates the polycondensation of croconic acid with squaryl dichloride. To carry out this polycondensation, 0.53 g of 3,4-dichloro-3-cyclobutene-1,2-dione (squaric acid dichloride) and 0.50 g of 4,5-dihydroxycyclopent-4-ene-1,2,3-trione were introduced into a 200 mL Schlenk tube. 30 mL of dry dimethylformamide (DMF) as hydrogen chloride acceptor and 10 mL of dry pyridine were added to the Schlenk tube under an inert atmosphere. The reaction was then stirred for 48 hours at a temperature of 60 °C using a magnetic bar. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was vigorously stirred for 15 minutes. The solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60° C. for 12 hours. (d) Polycondensation of 5,6-dihydroxycyclohex-5-ene-1,2,3,4-tetrone and squaryl dichloride - synthesis of poly(squaric acid-alt-5,6-dihydroxycyclohex-5-ene-1,2,3,4-tetrone) [ka]
[0104] This example illustrates the polycondensation of rhodizonic acid with squaryl dichloride. To carry out this polycondensation, 0.44 g of 3,4-dichloro-3-cyclobutene-1,2-dione (squaric acid dichloride) and 0.50 g of 5,6-dihydroxycyclohex-5-ene-1,2,3,4-tetrone were introduced into a 200 mL Schlenk tube. 30 mL of dry dimethylformamide (DMF) as hydrogen chloride acceptor and 10 mL of dry pyridine were added to the Schlenk tube under an inert atmosphere. The reaction was then stirred for 48 hours at a temperature of 60 °C using a magnetic bar. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was vigorously stirred for 15 minutes. The solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60° C. for 12 hours. (e) Polycondensation of tetrahydroxy-1,4-benzoquinone and squaryl dichloride - synthesis of poly(squaric acid-alt-tetrahydroxy-1,4-benzoquinone) [ka]
[0105] This example illustrates the polycondensation of tetrahydroxy-1,4-benzoquinone with squaryl dichloride. To carry out this polycondensation, 0.44 g of 3,4-dichloro-3-cyclobutene-1,2-dione (squaric acid dichloride) and 0.50 g of tetrahydroxy-1,4-benzoquinone were introduced into a 200 mL Schlenk tube. 30 mL of dry dimethylformamide (DMF) as hydrogen chloride acceptor and 10 mL of dry pyridine were added to the Schlenk tube under an inert atmosphere. The reaction was then stirred at a temperature of 60° C. using a magnetic bar for 48 hours. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was vigorously stirred for 15 minutes. The resulting solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60° C. for 12 hours.
[0106] The copolymer described in this example was characterized by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and the resulting spectrum is shown in FIG. (f) Polycondensation of 1,4-diaminoanthraquinone and squaryl dichloride - synthesis of poly(squaric acid amide) [ka]
[0107] This example shows the polycondensation of 1,4-diaminoanthraquinone with squaryl dichloride. To carry out this polycondensation, 1.3 g of squaryl dichloride and 2.29 g of 1,4-diaminoanthraquinone were introduced into a 200 mL Schlenk tube. 100 mL of dry dimethylformamide (DMF) as hydrogen chloride acceptor and 25 mL of dry pyridine were added to the Schlenk tube under an inert atmosphere. The reaction was then stirred at room temperature with a magnetic bar for 3 days. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was vigorously stirred for 15 minutes. The solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60° C. for 12 hours.
[0108] Copolymer 13 It was characterized by C solid-state nuclear magnetic resonance (NMR) spectroscopy (Figure 2) and ATR-FTIR (Figure 3). (g) Polycondensation of p-phenylenediamine (PPD) and diethyl squarate - synthesis of poly(squaramide) [ka]
[0109] 0.64 g of p-phenylenediamine (PPD) was added to a 10 mL stirred solution containing 1.0 g of diethoxy-3-cyclobutene-1,2-dione (or diethyl squarate) and 428 mg of zinc trifluoromethanesulfonate (zinc triflate) in a solvent containing toluene and dimethylformamide in a ratio of 9:1. The reaction was then stirred for 12 hours at a temperature of 100 °C using a magnetic bar. The solvent was removed using a rotary evaporator. Water (100 mL) was added to the resulting residue and the resulting slurry was stirred vigorously for 15 minutes. The solid was filtered and washed with water (5 times), followed by methanol (5 times) and toluene (5 times) until the filtrate was clear. The solid was then dried under vacuum at 60 °C for 12 hours. (h) Copolymerization with haloaromatic compounds - synthesis of aryl squarate copolymers [ka]
[0110] By adding 0.83 g of Ni(COD)2, 0.35 g of 1,5-cyclooctadiene and 0.47 g of 2,2'-bipyridine (bpy) in toluene, 0.3 equivalents of 3,4-dichloro-3-cyclobutene-1,2-dione and 0.3 equivalents of aromatic dibromide or aromatic dichloride relative to the catalyst are formed in situ. The reaction is then stirred at 60°C for 96 hours to obtain an insoluble polymer. The precipitate is washed with an aqueous ammonia solution and an aqueous solution of ethylenediaminetetraacetic acid disodium salt (EDTA disodium salt) at room temperature, then with water at a temperature of 50°C. The resulting polymer is then dried under vacuum at 60°C for 48 hours. In one example, the aromatic dibromide is 2,5-dibromothiophene. (i) Copolymerization with aromatic boronic acid ester compounds - synthesis of squaric acid thiophene copolymer [ka] - Preparation of thiophene-2,5-diboronic acid bis(pinacol) ester
[0111] The bis(pinacol)boronic ester is prepared according to the Miyaura reaction. In a glove box, anhydrous acetonitrile (45 mL), 2,5-dibromothiophene (0.7 mL) are introduced into a 100 mL Schlenk tube equipped with a septum, followed by bis(pinacolato)diboron (3.14 g), Pd2(Dba)3 (0.639 g), P(Ph)3 (0.647 g) and potassium acetate (1.85 g). The Schlenk tube is removed from the glove box while sealed and kept under argon. The reaction mixture is then stirred at 55° C. for 24 hours. Ethyl acetate (70 mL) is added and the mixture is filtered through Celite™. The filtrate is washed three times with water and five times with a 20% aqueous solution of Na2S2O3, followed by a 67% solution if the washings are still red. The mixture is then dried over MgSO4 and filtered. The filtrate is concentrated under vacuum on a rotary evaporator at 77°C. The mixture is passed through silica gel using an 80 / 20 mixture of hexane / ethyl acetate followed by a 60 / 40 mixture. The resulting solution is then concentrated in vacuum to give the product. 1 H and 13 Confirm by C NMR. - Preparation of copolymers
[0112] 0.225 g of 3,4-dichloro-3-cyclobutene-1,2-dione, 0.5 g of thiophene-2,5-diboronic acid bis(pinacol) ester and cesium carbonate are introduced into a Schlenk tube. A solvent (e.g., toluene) is added, followed by Pd2(Dba)3 and P(Ph)3. The reaction mixture is then stirred at 80°C for 4 days. A solution of methanol and hydrochloric acid (8:1) is added and stirred for 20 minutes. The mixture is filtered through a Büchner funnel and washed with methanol. The product is then dried in an oven at 80°C for 1 day. (j) Copolymerization with trialkyltin aromatic compounds - Synthesis of squaric acid thiophene copolymer [ka]
[0113] The cross-coupling polymerization reaction may proceed by Stille coupling. Under an inert atmosphere, 2,5-bis(tributylstannyl)thiophene and 3,4-dichloro-3-cyclobutene-1,2-dione are added to a Schlenk tube and dissolved in toluene. The resulting solution is degassed. Pd(PPh3)4 (0.1 eq.) and CuI (0.2 eq.) are added and the solution is stirred for a few minutes. CsF (4.4 eq.) is then added and the reaction is heated to reflux until completion as monitored by thin layer chromatography (TLC). After cooling, the mixture is concentrated in vacuo and the residue is dissolved in a minimum amount of dichloromethane and precipitated for purification. Example 3 Electrochemical properties - Cyclic voltammetry (a) Electrochemical properties of poly(squaric acid ester)
[0114] FIG. 1 shows cyclic voltammograms recorded for the copolymer prepared according to the procedure of Example 2(a) using lithium metal as the counter electrode and 1 M lithium hexafluorophosphate (LiPF6) in a carbonate-based solvent as the electrolyte. Results are shown at a rate of 2 mV / s, room temperature, and a potential sweep from 1 to 5 V (vs Li / Li+). The reaction between the squaric acid units and lithium (lithium insertion) was observed at a high voltage of 4.2 V. Thus, this polymer allows cycling of the battery at high voltages (i.e., higher than 3.8 V). The area under the cyclic voltammogram curve was used to calculate a specific capacity of 96 mAh / g. (b) Electrochemical properties of poly(squaric acid amide)
[0115] FIG. 2 shows cyclic voltammograms recorded for the copolymer prepared according to the procedure of Example 2(f) using lithium metal as the counter electrode and 1 M lithium hexafluorophosphate (LiPF6) in a carbonate-based solvent as the electrolyte. Results are shown at a rate of 2 mV / s, room temperature, and a potential sweep from 1 to 6 V (vs Li / Li+). FIG. 2 shows three lithium insertion peaks. One is assigned to the quinone moiety (2.8 V), a second to the 1,4-diaminophenyl moiety of 1,4-diaminoanthraquinone (3.7 V), and the last can be assigned to the squaric acid unit (4.4 V).
[0116] The area under the cyclic voltammogram curve was used to calculate a specific capacity of 692 mAh / g.
[0117] Besides lithium insertion at high voltages (up to 4.4 V in this example), another advantage of this polymer is that it can be designed depending on the monomer used in the copolymerization with squaric acid; this versatility allows for tuning of the reaction voltage.
[0118] Numerous modifications may be made to any of the above-described embodiments without departing from the scope of the invention. All references, patent or scientific literature materials mentioned in this application are incorporated herein by reference in their entirety for all purposes. The present invention provides, for example, the following items. (Item 1) Formula I: [ka] (In the formula, n and m are integers representing the number of each monomer unit in the polymer, where n>2 and m>0; X is independently in each occurrence an oxygen atom, a sulfur atom, or a group of the formula NR X and wherein the amine group is selected from the group consisting of p is an integer representing the number of X groups in each monomer unit and is 0 or 1; R 1is an optionally substituted conjugated non-aromatic cyclic group such as a quinone group, an optionally substituted aromatic or partially aromatic organic group, or combinations thereof in a polycyclic group; R x is a hydrogen atom or an optionally substituted alkyl. Polymer. (Item 2) R 1 is a monocyclic or polycyclic aromatic or partially aromatic organic group. (Item 3) R 1 3. The polymer according to claim 1 or 2, wherein (Item 4) 4. The polymer according to item 3, wherein each heterocycle contains 1 to 3 heteroatoms selected from N, S and O. (Item 5) 5. The polymer according to claim 4, wherein the heteroatom is N or S. (Item 6) Each substituted R 1 is substituted independently at each occurrence with one or more substituents selected from alkyl groups, alkoxy groups, nitrile groups, hydroxyl groups and halogen atoms, or with a protecting group if attached to a heteroatom such as a nitrogen group. (Item 7) 7. The polymer according to any one of the preceding claims, wherein the monocyclic or polycyclic aromatic or partially aromatic organic group is derived from one or more fused benzene rings, or one or more 5- or 6-membered fused rings, or a combination thereof. (Item 8) R 1 is selected from the group consisting of benzene, naphthalene, anthracene, benzoquinone, naphthoquinone and anthraquinone. (Item 9) 9. The polymer according to any one of the preceding claims, wherein p is 1 and X in each occurrence is an amine group (NH). (Item 10) p is 1, X in each occurrence is an amine group (NH), and R 1 Item 2. The polymer according to item 1, wherein is selected from the group consisting of paraphenylene and anthraquinone. (Item 11) 9. The polymer according to any one of the preceding claims, wherein p is 1 and X in each occurrence is an oxygen atom. (Item 12) p is 1, X in each occurrence is an oxygen atom, R 1 is selected from the group consisting of benzene, naphthoquinone, cyclohex-5-ene-1,2,3,4-tetrone, cyclopentene trione and 1,4-benzoquinone. (Item 13) p is 0 and R 1 is selected from the group consisting of benzene, phenylene, pyridine, thiophene, thienopyrroledione, benzothiophene, benzothiadiazole, 3,4-ethylenedioxythiophene, carbazole, dithiophene anthanthrone, dithiophenediketopyrrolopyrrole, isoindigo or indigo. (Item 14) 14. The polymer according to any one of the preceding claims, which is an alternating copolymer. (Item 15) Item 1. The polymer according to item 1, wherein m is 0 and said polymer of formula I is a homopolymer. (Item 16) [ka] Item 2. The polymer according to item 1, selected from (Item 17) [ka] Item 2. The polymer according to item 1, selected from (Item 18) [ka] Item 2. The polymer according to item 1, selected from (Item 19) [ka] (wherein Ar is an aryl divalent group). Item 2. The polymer according to item 1, selected from (Item 20) 20. The polymer according to any one of the preceding claims, for use in at least one element of an electrochemical cell selected from an electrode material and an electrolyte composition. (Item 21) 20. A process for producing a polymer according to any one of items 1 to 14 and 17 to 19, comprising the steps of: (a) Formulas II and III: [ka] (In the formula, X and R 1 is as defined in any one of items 1 to 15, Y, in each occurrence, is a leaving group selected from a halogen atom, a hydroxyl group, an amine group, and a lower alkoxy group; q is an integer representing the number of XH groups in the monomer unit of formula III and is at least 2; and reacting the monomer units of (b) isolating the polymer produced in step (a); A method comprising: (Item 22) 22. The method of claim 21, wherein Y is independently in each occurrence a chlorine atom, a bromine atom, an iodine atom, an amine group, a hydroxyl group or a lower alkoxy group. (Item 23) 23. The method according to item 21 or 22, wherein said monomeric unit of formula II is selected from 3,4-dihydroxy-3-cyclobutene-1,2-dione, 3,4-dimethoxy-3-cyclobutene-1,2-dione, 3,4-diethoxy-3-cyclobutene-1,2-dione, 3,4-diisopropoxy-3-cyclobutene-1,2-dione, 3,4-dibutoxy-3-cyclobutene-1,2-dione, 3,4-diamino-3-cyclobutene-1,2-dione, 3,4-dichloro-3-cyclobutene-1,2-dione, 3,4-dibromo-3-cyclobutene-1,2-dione and 3,4-diiodo-3-cyclobutene-1,2-dione. (Item 24) 24. The method according to any one of items 21 to 23, wherein the monomer unit of formula III is selected from p-phenylenediamine (PPD), benzene-1,4-diol, 5,8-dihydroxy-1,4-naphthoquinone, 5,6-dihydroxycyclohex-5-ene-1,2,3,4-tetrone, tetrahydroxy-1,4-benzoquinone, 1,4-diamino-2,3-dihydroanthraquinone and 4,5-dihydroxycyclopent-4-ene-1,2,3-trione. (Item 25) 25. The process according to any one of items 21 to 24, wherein step (a) is carried out in the presence of an organic base. (Item 26) 26. The method of claim 25, wherein the organic base comprises a tertiary amine. (Item 27) 27. The method according to item 26, wherein the tertiary amine is triethylamine, 2,6-lutidine or pyridine, preferably pyridine. (Item 28) 25. The process according to any one of items 21 to 24, wherein step (a) is carried out in the presence of a Lewis acid. (Item 29) 29. The method of claim 28, wherein the Lewis acid is selected from the group consisting of boron trifluoride etherate (BF3.OEt2), tin tetrachloride (SnCl4), zinc chloride (ZnCl2) and metal trifluoromethanesulfonates (triflates). (Item 30) 30. The method of claim 29, wherein the metal trifluoromethanesulfonate is selected from the group consisting of scandium(III) trifluoromethanesulfonate (Sc(OTf)3), magnesium trifluoromethanesulfonate (Mg(OTf)2), copper trifluoromethanesulfonate (Cu(OTf)2), and zinc trifluoromethanesulfonate (Zn(OTf)2). (Item 31) 31. The method of claim 30, wherein the Lewis acid is zinc trifluoromethanesulfonate (zinc triflate). (Item 32) 32. The process according to any one of items 21 to 31, wherein step (a) is carried out in the presence of a solvent. (Item 33) 33. The method of claim 32, wherein step (b) further comprises removing the solvent by evaporation. (Item 34) 34. The method according to claim 32 or 33, wherein the solvent is an organic polar aprotic solvent or a mixture comprising an organic polar aprotic solvent and a non-polar solvent. (Item 35) 35. The method of claim 34, wherein the organic polar aprotic solvent is dimethylformamide (DMF) or dimethylsulfoxide (DMSO). (Item 36) 34. The method of claim 32 or 33, wherein the non-polar solvent is toluene. (Item 37) 37. The method according to any one of items 31 to 36, wherein the polymer is produced by a polycondensation reaction. (Item 38) 18. A method for producing a polymer according to any one of items 1 to 14 and 17, comprising the steps of: (a) Formulas II and IV: [ka] (In the formula, R 1 is as defined in any one of items 1 to 15, Y, independently in each occurrence, is a leaving group selected from a chlorine atom, a bromine atom, and an iodine atom; Z is independently in each occurrence selected from the group consisting of chlorine atoms, bromine atoms, iodine atoms, boronic acids, boronic esters, and trialkyltin groups; r is an integer representing the number of Z in the monomer units of formula IV and is at least 2; and reacting the monomer units of (b) isolating the polymer produced in step (a); A method comprising: (Item 39) 39. The method according to item 38, wherein Y in each occurrence is a chlorine atom. (Item 40) 40. The method according to item 38 or 39, wherein the compound of formula IV is selected from formulae IV(a) to IV(o). (Item 41) The method according to any one of items 38 to 40, wherein Z is a chlorine atom in each occurrence. The method according to any one of items 38 to 40, wherein Z in each occurrence is a bromine atom. 43. The method according to any one of items 38 to 42, wherein step (a) further comprises reacting said monomeric unit of formula II with magnesium, thereby forming a Grignard reagent in situ prior to addition of said monomeric unit of formula IV. (Item 44) 44. The method according to any one of items 38 to 43, wherein step (a) is carried out in the presence of a catalyst. (Item 45) Item 45. The electrode material according to item 44, wherein the catalyst comprises a compound comprising a transition metal or a coordination complex comprising a transition metal or a transition metal. (Item 46) Item 46. The electrode material according to item 45, wherein the transition metal is selected from the group consisting of Ni, Pd, Co, Fe, Cr, Cu and Mn. (Item 47) Item 46. The electrode material according to item 45, wherein the transition metal is Ni or Pd. (Item 48) 48. The method according to any one of items 44 to 47, wherein the catalyst further comprises a trialkylphosphine or triphenylphosphine (PPh3), tetrahydrofuran (THF), 2,2'-bipyridine (bpy), CuI or KF. (Item 49) 48. The method according to any one of items 44 to 47, wherein the catalyst is selected from the group consisting of NiCl2(bpy), NiBr2(PPh3)2, PdCl2(bpy), Pd2(dba)3, Pd(PPh3)4, Pd(PPh3)2Cl2, PdFeEt2(bpy)2, CrMeCl2(THF)3, Ni(COD)(PPh3)2, Ni(COD)2(bpy), FeCl2, FeCl3 and CoCl2. (Item 50) 50. The method according to any one of items 44 to 49, wherein the catalyst is a complex comprising Ni(COD)(PPh3)2 in a ratio of 1:2. (Item 51) 50. The method according to any one of items 44 to 49, wherein the catalyst is a complex comprising Ni(COD)2, 1,5-cyclooctadiene nickel and bpy in a ratio of 1:1:1. (Item 52) 52. The method according to any one of items 38 to 51, wherein step (a) is carried out in the presence of a solvent. (Item 53) 53. The method of claim 52, wherein step (b) further comprises removing the solvent by evaporation. (Item 54) 54. The method according to claim 52 or 53, wherein the solvent is an organic polar aprotic solvent or a non-polar solvent. (Item 55) 55. The method of claim 54, wherein the organic polar aprotic solvent is tetrahydrofuran (THF). (Item 56) 55. The method of claim 54, wherein the non-polar solvent is toluene. (Item 57) 20. An electrode material comprising the polymer according to any one of items 1 to 19. (Item 58) Electrochemical active material and optionally further comprising a binder, an electronically conductive material, or a combination thereof. (Item 59) The electrochemical active material is selected from the group consisting of metal oxide particles, lithiated metal oxide particles, metal phosphate particles and lithiated metal phosphate particles. (Item 60) Item 60. The electrode material according to item 59, wherein the metal is a transition metal selected from the group consisting of iron (Fe), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co) and combinations of at least two thereof. (Item 61) The polymer is active material 61. The electrode material according to any one of items 58 to 60, wherein the electrode material is grafted to (Item 62) 61. The electrode material according to any one of items 58 to 60, wherein the polymer is the binder. (Item 63) The polymer is active material Item 59. The electrode material according to item 58, wherein (Item 64) The electrochemical active material 64. The electrode material according to any one of items 58 to 63, wherein both the binder and the polymer comprise the polymer. (Item 65) 65. The electrode material according to any one of items 57 to 64, further comprising an oxide of a transition metal, for example the transition metal being selected from the group consisting of titanium (Ti), manganese (Mn), and cobalt (Co). (Item 66) 66. A positive electrode comprising the electrode material according to any one of items 57 to 65 on a current collector. (Item 67) 20. An electrolyte composition comprising the polymer and a salt according to any one of the preceding items. (Item 68) Item 69. The electrolyte composition according to item 67, wherein the electrolyte is a solid polymer electrolyte (SPE). 68. The electrolyte composition according to item 67, which is a gel electrolyte composition. (Item 70) 20. An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein at least one of the positive electrode or the electrolyte comprises the polymer according to any one of the preceding claims. (Item 71) 70. An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, said electrolyte being as described in any one of items 67 to 69. (Item 72) 72. The electrochemical cell according to item 70 or 71, wherein the positive electrode is as described in item 65. (Item 73) 73. The electrochemical cell of any one of items 70 to 72, wherein the negative electrode is an alkali metal film. (Item 74) 74. The electrochemical cell of item 73, wherein the alkali metal film is a metallic lithium film or an alloy thereof. (Item 75) 75. A battery comprising at least one electrochemical cell according to any one of items 70 to 74. (Item 76) 76. The battery according to item 75, selected from a lithium battery, a sodium battery and a magnesium battery. (Item 77) 20. A polymer according to any one of the preceding claims for use in a polymer-based optoelectronic device. (Item 78) 78. The polymer according to item 77, wherein the polymer-based optoelectronic device is selected from the group consisting of an electrochromic device (ECD), a photochromic device, an organic light-emitting diode (OLED) and a solar cell. (Item 79) 20. An optoelectronic device comprising a polymer according to any one of items 1 to 19. (Item 80) 80. The optoelectronic device according to item 79, wherein the polymer-based optoelectronic device is selected from the group consisting of an electrochromic device (ECD), a photochromic device, an organic light-emitting diode (OLED) and a solar cell.
Claims
1. 1. An electrochemical cell comprising a positive electrode, a negative electrode, and an electrolyte, wherein said elements are represented by Formula I: 【Chemical 33】 (In the formula, n and m are integers representing the number of each monomer unit in the polymer, where n>2 and m>0; X is independently in each occurrence an oxygen atom, a sulfur atom, or a group of the formula NR X and wherein the amine group is selected from the group consisting of p is an integer representing the number of X groups in each monomer unit and is 0 or 1; R 1 is a substituted or unsubstituted conjugated non-aromatic cyclic group, a substituted or unsubstituted aromatic or partially aromatic organic group, or a combination thereof in a polycyclic group; R x is a hydrogen atom or a substituted or unsubstituted alkyl. The polymer comprises wherein said element is an electrode material of said positive electrode and said polymer is an electrochemically active material of said electrode material; element.
2. R 1 The element of claim 1 , wherein is a heterocyclic compound.
3. Each substituted R 1 is substituted independently at each occurrence with one or more substituents selected from alkyl groups, alkoxy groups, nitrile groups, hydroxyl groups and halogen atoms, or, if attached to a heteroatom, with a protecting group.
4. R 1 4. The element of claim 1, wherein is selected from the group consisting of benzene, naphthalene, anthracene, benzoquinone, naphthoquinone, and anthraquinone.
5. (i) p is 1 and X in each occurrence is an amine group (NH); or (ii) p is 1 and X in each occurrence is an oxygen atom; or (iii) p is 0 and R 1 The element of any one of claims 1 through 3, wherein is selected from the group consisting of benzene, pyridine, thiophene, thienopyrroledione, benzothiophene, benzothiadiazole, 3,4-ethylenedioxythiophene, carbazole, dithiophene anthanthrone, dithiophenediketopyrrolopyrrole, isoindigo, and indigo.
6. The polymer is 【Chemistry 41】 【Chemistry 42】 【Chemical 37】 (wherein Ar is an aryl divalent group). The element of claim 1 selected from:
7. m is 0 and said polymer of formula I is 【Chemical 34】 The element of claim 1 which is a homopolymer selected from:
8. 8. The element of claim 1, wherein the element is an electrode material and further comprises an electrochemically active material in addition to the polymer.
9. A positive electrode comprising the element of claim 8 on a current collector.
10. 8. An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode comprises an element according to any one of claims 1 to 7.
11. A battery comprising at least one electrochemical cell according to claim 10.
Citation Information
Patent Citations
Conjugated polymer containing 1, 2-squaric acid and preparation method and application thereof
CN102516504A
Polyalkyl-fluorene conjugated polymer and use
CN1438254A
N-type conductive polymer and production thereof
JP1994256478A
Conductive alternating copolymer and its production
JP1995252350A
Particle materials
JP2007536425A